P 144 Longer-term spatial navigation deficits in transient global amnesia – a follow-up study. Issue 10 (October 2017) - Zwergal, A.; Irving, S.; Trapp, C.; Pradhan, C.; Dieterich, M.; Brandt, T.; Schöberl, F.
Abstract : Introduction: Transient global amnesia (TGA) is a neurological syndrome that typically presents with sudden and severe anterograde amnesia and spatial orientation deficits. Although acute symptoms last for less than 24 h, subtle deficits may persist longer. The aim of the current study was to investigate spatial orientation performance in a real world environment longitudinally after onset of TGA. Methods: We present the results of 19 healthy subjects and 21 TGA patients, who completed a spatial navigation task in a real-space environment. The TGA patients performed the task on two occasions, firstly within ∼ 3.15 days of their attack (post-acute TGA), secondly a follow up repetition (follow up) some months later. The spatial navigation task consisted of 5 distributed target items in a novel environment. In the exploration phase (10 min) of the task, the examiner took the subject to the exact location of each target item. In the navigation phase (10 min) the subject had to find each target item in a pseudo-randomised order. Throughout, the subjects wore a gaze-controlled head camera, allowing recording of individual "navigograms" for visual exploration, trajectory, and gaze behaviour. An MRI was done in all patients during the acute phase of the TGA. Results: Post-acute TGA patients showed a significantly worse spatial navigation performance when compared to healthy controls ( p < 0.005); error rates decreased in the follow up examination (37% in the post-acute phase versus 25% in follow up), but were still significantly higher than in healthy controls (4%, p < 0.04). Subgroup analyses showed that TGA patients with hippocampal diffusion lesions did not have a higher error rate than patients without lesions. Age differences were significant; younger patients outperformed older patients. Navigograms showed that all patients with TGAs did not make use of short cuts between stimuli and had a longer duration of stay at way crossings. Discussion: The higher number of error rates and non-use of short cuts during the task suggest that post-acute TGA patients are unable to generate cognitive maps of their environment. Spatial navigation deficits are - although to a lesser extent - still present several months after the initial presentation of symptoms, despite subjective memory symptoms have gone. These data challenge the concept of TGA as a short-lasting transient syndrome and indicate a longer-lasting hippocampal pathology in this disorder.